CHARACTERIZATION OF A FUNCTIONAL VANADIUM-DEPENDENT BROMOPEROXIDASE IN THE MARINE CYANOBACTERIUM SYNECHOCOCCUS SP. CC9311(1) - Johnson, Todd L (Journal of phycology, 2011)
© 2011 Phycological Society of America.